Keselamatan Pengguna Jalan di Jakarta Timur - Saidah, Deslida; Mafrudoh, Luth; Fitrina, Rehani (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2018)
Jakarta as a capital city has many problems with transportation and facilities for road users. The purpose of this study is to determine the effect of facilities, facilities and infrastructure on safety of road users in East Jakarta (case study of Cililitan Terminal - Rawamangun Terminal). The method used was quantitative and qualitative and the sampling method used purposive and saturated sampling as much as 178 samples Data analysis techniques consisted of validity test, reliability test and variable descriptive statistics. The result of the study reveals that there are strong influences on safety facilities, facilities and infrastructure for Road users.